2018
DOI: 10.1161/jaha.117.007920
|View full text |Cite
|
Sign up to set email alerts
|

Non–ST‐Segment–Elevation Myocardial Infarction Among Patients With Chronic Kidney Disease: A Propensity Score–Matched Comparison of Percutaneous Coronary Intervention Versus Conservative Management

Abstract: BackgroundChronic kidney disease (CKD) remains an independent predictor of cardiovascular morbidity and mortality. CKD complicates referral for percutaneous coronary intervention (PCI) in non–ST‐segment–elevation myocardial infarction (NSTEMI) patients because of the risk for acute kidney injury and the need for dialysis, with American College of Cardiology/American Heart Association guidelines underscoring the limited data on these patients.Methods and ResultsUsing the National Inpatient Sample to analyze hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…We observed that in non-ST-segment elevation AMI admissions with CKD stages 4 and 5 had 41% and 20% less likelihood, respectively, of undergoing PCI compared with those with no CKD. The cohort treated with PCI had lower in-hospital mortality compared to those managed medically across all CKD stages [8]. Similarly, this current study confirms what prior studies have shown that patients with CKD/ESRD tend to receive less coronary angiography, PCI and MCS.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We observed that in non-ST-segment elevation AMI admissions with CKD stages 4 and 5 had 41% and 20% less likelihood, respectively, of undergoing PCI compared with those with no CKD. The cohort treated with PCI had lower in-hospital mortality compared to those managed medically across all CKD stages [8]. Similarly, this current study confirms what prior studies have shown that patients with CKD/ESRD tend to receive less coronary angiography, PCI and MCS.…”
Section: Discussionsupporting
confidence: 87%
“…Using the HCUP-NIS data from 2005–2016, a retrospective cohort study of admissions with AMI in the primary diagnosis field (International Classification of Diseases 9.0 Clinical Modification [ICD-9CM] 410.x and ICD-10CM I21.x-22.x) and a secondary diagnosis of CS (ICD-9CM 785.51, ICD-10CM R57.0) were identified [ 24 ]. Similar to prior literature, prior CKD/ESRD was identified using ICD-9CM 585.x and ICD-10CM N18.x codes [ 8 ]. The use of chronic dialysis was identified using ICD-9CM 39.95/ICD-10CM 5A1D70Z, 5A1D80Z, 5A1D90Z (hemodialysis) and ICD-9CM 54.98/ICD-10CM 3E1M39Z (peritoneal dialysis) in the absence of a concomitant diagnosis of AKI [ 5 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic kidney disease (CKD) is an independent risk factor for AMI and the risk increases with advanced renal insufficiency [2,3]. Additionally, AMI patients comorbid with CKD are not ideal patients for coronary angiography and percutaneous coronary intervention, therefore having higher mortality rates than AMI patients without CKD [2,[4][5][6][7][8]. Furthermore, AMI patients comorbid with advanced CKD have a higher rate of long-term adverse cardiac events than those with normal kidney function [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, percentage of smoking habit significantly decreased recently. Additionally, in the years 2005-2014 numerous changes in the clinical profile (mean age, gender, comorbidities and Killip class on admission) that might have impact on prognosis were noted[9][10][11][12][13].…”
mentioning
confidence: 99%